On the question of gambling in giving prizes to the holders of savings certificates: an Islamic analysis on Malaysian practice - Md. Sawari, Mohd. Fuad; Hassan, Razi; Abdullah, Faruk (Institute of Interdisciplinary Business Research, 2010)

(untitled)
The focal point of this paper is to analyze the issue of gambling in the practice of prize-giving to the selected holders of Premium savings Certificate (PSC), a product offered by Bank Saimpanan Nasional (BSN), the national savings bank of Malaysia. The paper attempts to provide the Islamic juristic decision on this issue. The paper finds that based on the analogical reasoning of the Shari ah, PSC has different characteristics from gambling. Moreover, a number of fatwa issued by the scholars from Malaysia affirm that, there is no existence of gambling in PSC. The paper adopts descriptive and analytical methods. It relies on the classical and contemporary Arabic literatures as well the Malay and English literatures. Furthermore, interview method is used, in order to obtain first hand information. Understanding the Shari ah ruling pertaining to the gambling issue of PSC has a great impact on the Muslim community to decide whether they will purchase this product or reject it. The paper would be a refereed literature to understand the Shari ah appraisal of giving prizes to the holders of savings certificates. The study is limited to the gambling issue and recommends further study on the underlying contract and the field of investment of PSC.